PERENCANAAN STRATEGIS SISTEM INFORMASI UNTUK MENINGKATKAN JUMLAH PENDAFTARAN CALON MAHASISWA (PCM) DAN KEUNGGULAN KOMPETITIF DI STKOM AL MA’SOEM - Firman Hamdani (Masoem University, 2018)
@font-face font-family:"Times New Roman"; @font-face font-family:"??"; p.MsoNormal mso-style-name:Normal; mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; font-family:'Times New Roman'; font-size:12,0000pt; p.MsoFooter mso-style-name:Footer; margin:0pt; margin-bottom:.0001pt; font-family:'Times New Roman'; font-size:12,0000pt; span.msoIns mso-style-type:export-only; mso-style-name:""; text-decoration:underline; text-underline:single; color:blue; span.msoDel mso-style-type:export-only; mso-style-name:""; text-decoration:line-through; color:red; @pagemso-page-border-surround-header:no; mso-page-border-surround-footer:no;@page Section0 div.Section0page:Section0;Al Ma’soem STKOM is one of the Universities under the auspices of the Al Ma’soem Bandung Foundation. STKOM has two study programs, namely Information Systems (S1 & D3) and Accounting Information Systems (D3). With the existence of similar Colleges, it is a challenge for STM Al Ma’soem to increase the number of new Student Candidates (PCMs) each year by increasing the competitive advantage of other Universities. Al Ma'soem's STKOM currently uses information systems in website-based academic and promotional services, but does not yet have an information system strategic plan that can certainly be left behind by other competitors if IS / IT strategic planning is not used in carrying out academic services and activities. PCM. This study aims to analyze and design frameworks of strategic information systems planning to increase the number of PCM and competitive advantage. In this study carried out with the John Ward methodology approach, Pepprad. The methodology used consists of two stages. 1. Stages of input, including: Analysis of the internal business environment, Analysis of the external business environment, internal SI / IT environmental analysis, external IS / IT environment analysis. 2. Output stages, including: Business SI Strategy, IT Strategy and IS / IT Management Strategy. The results of the IS / IT strategic planning are in the form of application portfolios, which are expected to be implemented according to the information system requirements for the next five years. The results of this study are expected to be beneficial for all parties, among others, for the Al Ma'soem STKOM, the PCM Committee, the academic community, namely Managers, Lecturers, Students and Prospective Students. so that increased competitive advantage can be more effective and efficient which can increase the number of new PCMs every year.